Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\frac{2x^2y-3xy}{4x^2+x}=\frac{xy\left(2x-3\right)}{x\left(4x+1\right)}\)\(=\frac{y\left(2x-3\right)}{4x+1}\)
b)\(\frac{3x^2+x-2}{x+1}=\frac{\left(x+1\right)\left(3x-2\right)}{x+1}=3x-2\)
a) x2(5x3 – x - \(\frac{1}{2}\)) = x2. 5x3 + x2 . (-x) + x2 . ( \(-\frac{1}{2}\) )
= 5x5 – x3 – \(\frac{1}{2}\)x2
b) (3xy – x2 + y) \(\frac{2}{3}\)x2y = \(\frac{2}{3}\)x2y . 3xy + \(\frac{2}{3}\)x2y . (- x2) + \(\frac{2}{3}\)x2y .
y = 2x3y2 – \(\frac{2}{3}\)x4y + \(\frac{2}{3}\)x2y2
c) (4x3– 5xy + 2x)( \(-\frac{1}{2}\)xy) = \(-\frac{1}{2}\)xy . 4x3 + ( \(-\frac{1}{2}\)xy) . (-5xy) + ( \(-\frac{1}{2}\)xy) . 2x
= -2x4y + \(\frac{5}{2}\)x2y2 – x2y.
a, (-2x5+3x2-4x3):2x2=-x3+3/2-2x=-x3-2x+3/2
b,(x3-2x2y+3xy2):(-1/2.x)=-2x2+4xy-6y2
c,(3x2y2+6x2y3-12xy):3xy=xy+2xy2-4
a) -2x5 + 3x2 - 4x3 = x2. (-2x3 + 3 - 4x) => (-2x5 + 3x2 - 4x3 ) : 2x2 = [ x2. (-2x3 + 3 - 4x) ] : (2x2) = (-2x3 + 3 - 4x) /2 = -x3 - 2x + (3/2)
b) x3 - 2x2y + 3xy2 = x. (x2 - 2xy + 3y2)
=> x3 - 2x2y + 3xy2 : (-1/2. x) = (x2 - 2xy + 3y2) : (-1/2) = (x2 - 2xy + 3y2) . (-2) =-2 x2 + 4xy -6y2
c) 3x2y2 + 6x2y3 - 12xy = 3xy. (xy + 2xy2 - 4)
=> 3x2y2 + 6x2y3 - 12xy : 3xy = xy + 2xy2 - 4
\(\left(2x^2y-3xy\right)\times\left(4x^2+x\right)\)
\(=8x^4y+2x^3y-12x^3y-3x^2y\)
\(=8x^4y-10x^3y-3x^2y\)
(2x2y-3xy).(4x2+x)=(8x4y+2x3y)-(12x3y+3x2y)
=8x4y+2x3y-12x3y-3x2y
=8x4y-10x3y-3x2y